Fuzzy approach for toffoli gate in quantum computation with mixed states - Freytes Solari, Hector Carlos (2014)
In the framework of quantum computation with mixed states, a fuzzy representation based on continuous t-norms for Toffoli gate is introduced. In this representation, the incidence of nonseparability is specially investigated